Management Challenges for Academic Improvement in Higher Education in The Digital Era - Antono Damayanto; B.M.A.S. Anaconda Bangkara; Ali Zaenal Abidin; Ani Heryani; Irma Rachmawati Maruf (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
We believe that we can get relevant answers for this study by providing accurate data from studies by field experts. We get supporting data from several thieves and electronically in databases of scientific journals, books, and websites that discuss issues where governance challenges improve academic learning outcomes in the tall tree in the digital era. Furthermore, we reviewed the data using a phenomenological approach, namely obtaining as much data as possible and interpreting it to produce highly accurate and valid data. This study relies heavily on previous studies' peer data or secondary data communication. The way to get it is to search digitally using the keyboard on the school's Google search engine on several well-known publications such as Eric, Taylor, and Francis and several literature databases from national journals. We can conclude that the management of academic improvement can be done by exploring digital and other technological devices based on experts' advice. We hope this result will be helpful in the following studies.